2010
DOI: 10.1111/j.1365-2567.2009.03238.x
|View full text |Cite
|
Sign up to set email alerts
|

Cholinergic stimulation of the immune system protects against lethal infection by Salmonella enterica serovar Typhimurium

Abstract: SummaryThe cholinergic nervous system has been demonstrated to attenuate the inflammatory response during sepsis via the inhibitory action of acetylcholine (ACh) on macrophages. These findings were largely based on experimental sepsis models using endotoxin as the inducing agent. Herein, however, we report that the specific inhibition of acetylcholinesterase (AChE) renders animals more resistant to infection by a virulent strain of Salmonella enterica serovar Typhimurium, a Gram-negative enteric pathogen. Inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 59 publications
0
28
0
1
Order By: Relevance
“…Thus, in a recent randomized controlled trial, critically ill patients with delirium receiving a cholinesterase inhibitor (rivastigmine) had greater mortality than participants not treated with this drug . Alternatively, recent experimental evidence shows that administration of AChE inhibitors suppresses systemic inflammation and enhances survival of animals exposed to lipopolysaccharides or infection . These conflicting results demonstrate that any modulation of the cholinergic system should take into account the complex regulatory mechanisms determining the participant's baseline immune set point and the magnitude of responsiveness to inflammatory challenge.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, in a recent randomized controlled trial, critically ill patients with delirium receiving a cholinesterase inhibitor (rivastigmine) had greater mortality than participants not treated with this drug . Alternatively, recent experimental evidence shows that administration of AChE inhibitors suppresses systemic inflammation and enhances survival of animals exposed to lipopolysaccharides or infection . These conflicting results demonstrate that any modulation of the cholinergic system should take into account the complex regulatory mechanisms determining the participant's baseline immune set point and the magnitude of responsiveness to inflammatory challenge.…”
Section: Discussionmentioning
confidence: 99%
“…Chiarla and colleagues identified a significant decrease in the cholinesterase activity of patients in a critical condition, in particular, patients with sepsis or liver dysfunction [30]. Fernandez-Cabezudo and colleagues have shown that cholinergic stimulation of the immune system has a protective effect against salmonella infections [31].…”
Section: Discussionmentioning
confidence: 99%
“…The nervous system is also a regulator of GIT immune responses via neuro-immune synapses, via the modulation of bacterial toxin detection or adherence [34,35]. Some authors have found that stress neuroendocrine mediators such as catecholamine and the adrenocorticotropic hormone (ACTH) can influence the binding and adherence of pig enteric pathogens to the intestinal mucosa [34][35][36][37][38]. Medland et al [39] found significant alterations in ENS phenotype and function in response to weaning.…”
Section: Enteric Nervous Systemmentioning
confidence: 99%